Sensitivity of salmonella YG5161 for detecting PAH‐associated mutagenicity in air particulate matter. (28th February 2014) - Umbuzeiro, Gisela A.; Kummrow, Fábio; Morales, Daniel Alexandre; Alves, Debora Kristina M.; Lim, Hwanmi; Jarvis, Ian W.H.; Bergvall, Christoffer; Westerholm, Roger; Stenius, Ulla; Dreij, Kristian
<x xml:space="preserve">Abstract</x> The Salmonella/microsome assay is the most used assay for the evaluation of air particulate matter (PM) mutagenicity and a positive correlation between strain TA98 responses and benzo[a]pyrene (B[a]P) levels in PM has been found. However, it seems that the major causes of PM mutagenicity in this assay are the nitro and oxy‐PAHs. Salmonella YG5161, a 30‐times more responsive strain to B[a]P has been developed. To verify if YG5161 strain was sufficiently sensitive to detect mutagenicity associated with B[a]P mutagenicity, PM samples were collected in Brazil and Sweden, extracted with toluene and tested in the Salmonella/microsome microsuspension assay. PAHs and B[a]P were determined and the extracts were tested with YG5161 and its parental strain TA1538. The extracts were also tested with YG1041 and its parental strain TA98. For sensitivity comparisons, we tested B[a]P and 1‐nitropyrene (1‐NP) using the same conditions. The minimal effective dose of B[a]P was 155 ng/plate for TA1538 and 7 ng/plate for YG5161. Although the maximum tested dose, 10 m3/plate containing 9 ng of B[a]P in the case of Brazilian sample, was sufficient to elicit a response in YG5161, mutagenicity was detected at a dose as low as 1 m3/plate (0.9 ng). This is probably caused by nitro‐compounds that have been shown to be even more potent than B[a]P for YG5161. It seems that the mutagenicity of B[a]P present in PM is not detectable even with the use of YG5161 unless more efficient separation to remove the nitro‐compounds from the PAH extract is performed. Environ. Mol. Mutagen. 55:510–517, 2014. © 2014 Wiley Periodicals, Inc.